ADAB MURID DALAM PENDIDIKAN SPIRITUAL MEURUT SYEKH ‘ABDUL QĀDIR AL JĪLĀNĪ (1077-1166) DAN AL HABĪB ‘ABDULLAH ‘ALAWĪ AL HADDĀD (1634-1720) - Hilmi Yusron (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2021)
This study analyzes the thoughts of Sheikh 'Abdul Qadïr al jailïnandHabib Abdullah bin Alawi Al-Haddad on the Discipline of Spiritual Education students. The purpose of this study is to determine the concept of Disciples in Spiritual Education according to Sheikh 'Abdul Qadïr al jailïn and Habib Abdullah 'Alawi Al-Haddad. To find out the Characteristics of Students in Education according to Sheikh 'Abdul Qadïr al jailïn and Habib Abdullah 'Alawi Al-Haddad in educational institutions today. This type of research uses literature. The results of the study show that the Discipline of Disciples in Spiritual Education according to Sheikh 'Abdul Qadïr al jailïn and Habib Abdullah 'Alawi Al-Haddad is a description of Disciples' Ethics in Spiritual Education to focus on fixed values ​​in the corridors of the Qur'an and Sunnah, Purification of the soul before starting the Journey to Allah. The research method used is library research. The main source is the book Al Gunyah Li Talibi Tariq Al Haqq, Risalah Adab SulŪk Al myrrhïd and the supporting source is the translation of the Treatise of Adab Sulūk Al myrrhïd and books related to the material. The technical data analysis uses the content analysis method.